Radiation risks of lymphoma and multiple myeloma incidence in the updated NRRW-3 cohort in the UK: 1955–2011. (18th January 2022) - Hunter, Nezahat; Haylock, Richard
Abstract: The effect of external radiation on lymphoma, including non-Hodgkin lymphoma (NHL), Hodgkin lymphoma (HL) and multiple myeloma (MM) incidence was evaluated in the National Registry for Radiation Workers based upon the third analysis cohort but with an additional 10 years of follow-up. The study includes 172 452 workers, of whom (90%) were men with 5.25 million person-years of follow-up from 1955 through to the end of 2011. A total of 711 cases of NHL, 113 cases of HL and 279 cases of MM were registered. Poisson regression was used to estimate the excess relative risk per unit of cumulative exposure to ionising radiation. A statistically significant association was found between radiation dose and the incidence of NHL and MM. There was no evidence of radiation associated excess risk for HL. The reported associations are based on a very small proportion of exposed workers, in particular among workers with cumulative doses above 0.5 Sv so should be treated with caution, further investigations are necessary to confirm our results.